2019
DOI: 10.1021/acsnano.9b00892
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Magnetosomes for Ferroptosis/Immunomodulation Synergism in Cancer

Abstract: As traditional anticancer treatments fail to significantly improve the prognoses, exploration of therapeutic modalities is urgently needed. Herein, a biomimetic magnetosome is constructed to favor the ferroptosis/immunomodulation synergism in cancer. This magnetosome is composed of an Fe3O4 magnetic nanocluster (NC) as the core and pre-engineered leukocyte membranes as the cloak, wherein TGF-β inhibitor (Ti) can be loaded inside the membrane and PD-1 antibody (Pa) can be anchored on the membrane surface. After… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
220
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 301 publications
(221 citation statements)
references
References 38 publications
1
220
0
Order By: Relevance
“…Bioengineered MTB are used to produce magnetosomes with diverse shapes and narrow distribution of crystal size as well as specific functions, which make them ideal as image contrasting agents. These custom‐tailored magnetosomes have been intensively investigated for MRI‐based detection of cancerous cells in experimental tumor models, [ 320–324 ] Bioengineering of MTB may be achieved using methods that include direct chemical modification, genetic engineering, and hybrid modification ( Figure A). With the advancement of nanotechnology, magnetosomes may be functionalized with different ligands such as enzymes, proteins, nucleic acids, green‐fluorescent protein, antibodies, and drugs (Figure 16B) [ 325 ] for multifunctional applications (Figure 16C).…”
Section: Applicationsmentioning
confidence: 99%
“…Bioengineered MTB are used to produce magnetosomes with diverse shapes and narrow distribution of crystal size as well as specific functions, which make them ideal as image contrasting agents. These custom‐tailored magnetosomes have been intensively investigated for MRI‐based detection of cancerous cells in experimental tumor models, [ 320–324 ] Bioengineering of MTB may be achieved using methods that include direct chemical modification, genetic engineering, and hybrid modification ( Figure A). With the advancement of nanotechnology, magnetosomes may be functionalized with different ligands such as enzymes, proteins, nucleic acids, green‐fluorescent protein, antibodies, and drugs (Figure 16B) [ 325 ] for multifunctional applications (Figure 16C).…”
Section: Applicationsmentioning
confidence: 99%
“…It has been shown that blocking PD‐1/PD‐L1 checkpoints promotes antitumor immunity by inhibiting the depletion of effector T cells, particularly after combination with other treatments, greatly improving the antitumor efficacy. [ 42 ] Thereby, we further employed PD‐1 blockade to increase the antitumor effect of Fe 3 O 4 ‐SAS@PLT‐mediated ferroptosis. Before investigating the potential anti‐metastatic effect, the circulation and biodistribution of Fe 3 O 4 ‐SAS@PLT in 4T1 metastatic tumor‐bearing mice were initially evaluated with an inductively couple plasma spectrometer.…”
Section: Resultsmentioning
confidence: 99%
“…In turn, tumor antigen released from dead cells could improve the immunogenicity, thus forming a cyclical therapeutic reaction in TME. In vitro and in vivo studies showed that this nano magnetosome can not only inhibit tumor growth and metastasis, but also suppressed the postoperative recurrence of tumors …”
Section: Ferroptosis Inducers For Cancer Therapymentioning
confidence: 99%
“…F) Bioluminescence of primary tumors before (−1 d) and after (0 d) resection, as well as recurrence (18 d) in B16F10 xenograft mice under indicated treatments. Reproduced with permission . Copyright 2019, American Chemical Society.…”
Section: Ferroptosis Inducers For Cancer Therapymentioning
confidence: 99%